2019
DOI: 10.1155/2019/8395389
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lung Adenocarcinoma Originating from an Old Posttraumatic Scar in a Young Patient

Abstract: A relationship between lung scarring and cancer has been recognized for many decades but more evidence is needed to strengthen this association. A 34-year-old nonsmoker male with a history of left lower lobe lung scar secondary to a pulmonary contusion from a motor vehicle accident in 2012 was admitted with shortness of breath and cough. A computed tomography (CT) angiography of the chest demonstrated bilateral pulmonary emboli, left lower lobe mass, left lung septal thickening, and mediastinal lymphadenopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…The presentation of cutaneous metastasis in surgical scar tissue secondary to resection of the primary tumor has been described in cases of colon, breast, and endometrial cancer [10][11][12]. Lung adenocarcinoma arising in prior surgical and post-traumatic scars have been reported [13]. These reports suggest surgical scar metastasis arise as a result of inoculation of the surgical site by the primary tumor during resection.…”
Section: Case Discussionmentioning
confidence: 99%
“…The presentation of cutaneous metastasis in surgical scar tissue secondary to resection of the primary tumor has been described in cases of colon, breast, and endometrial cancer [10][11][12]. Lung adenocarcinoma arising in prior surgical and post-traumatic scars have been reported [13]. These reports suggest surgical scar metastasis arise as a result of inoculation of the surgical site by the primary tumor during resection.…”
Section: Case Discussionmentioning
confidence: 99%
“…Several studies have suggested that lung cancer following pulmonary TB is not of bronchial in origin and rather arise from the scar tissue [8,9]. Furthermore, upper lobes are commonly affected compared to other regions [8,9]. Literature review revealed conflicting evidence on the histological subtypes of lung cancer related to TB.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on preexisting TB and lung cancer risk showed that only adenocarcinoma was associated with TB [1]. Furthermore, studies have shown that cancer occurring in a scarred lung were usually adenocarcinoma [8,9]. Based on the above literature, it seems that squamous cell carcinoma is common in concurrent cancers and adenocarcinoma in subsequent cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, en 2010 se publicó el caso de un carcinoma con triple diferenciación (adenocarcinoma, escamoso y células pequeñas) asentado sobre una cicatriz fibroelástica con calcificaciones (8) . De manera más infrecuente, existen reportes de CCP desarrollados a partir de contusiones pulmonares antiguas en pacientes jóvenes con antecedentes de traumatismo (9) . Sin embargo, a nuestro conocimiento, es el primer reporte de caso de CCP sobre la cicatriz de un postoperatorio alejado de cirugía pulmonar por patología benigna.…”
Section: Discussionunclassified